RAS: Striking at the Core of the Oncogenic Circuitry - Gimple, Ryan C.; Wang, Xiuxing (Frontiers in Oncology, 2019)
Cancer is a devastating disease process that touches the lives of millions worldwide. Despite advances in our understanding of the genomic architecture of cancers and the mechanisms that underlie cancer development, a great therapeutic challenge remains. Here, we revisit the birthplace of cancer biology and review how one of the first discovered oncogenes, RAS, drives cancers in new and unexpected ways. As our understanding of oncogenic signaling has evolved, it is clear that RAS signaling is not homogenous, but activates distinct downstream effectors in different cancer types and grades. RAS signaling is tightly controlled through a series of post-transcriptional mechanisms, which are frequently distorted in the context of cancer, and establish key metabolic and immunologic states that support cancer growth, migration, survival, metastasis, and plasticity. While targeting RAS has been fiercely pursued for decades, new strategies have recently emerged with the potential for therapeutic efficacy. Thus, understanding the complexities of RAS biology may translate into improved therapies for patients with RAS-driven cancers.